The triterpenoid alpha, beta-amyrin prevents the impaired aortic vascular reactivity in high-fat diet-induced obese mice - Santos, Flávia Almeida (2017)
To characterize the pro tective effects of the triterpenoid mixture alpha, beta-amyrin (AMY, 20 mg/kg, during 15 days) on the reactivity of isolated aorta of high- fat diet (HFD)-induced obese mice. Male Swiss mice were fed with HFD or normal diet (ND) for 15 weeks. Contractions of thoracic aorta in response to KCl or phen- ylephrine (PHE) and relaxation by acetylcholine (ACh) or sodium nitroprusside (SNP) were analyzed. HFD-fed mice developed hyperglycemia, hyperlipidemia, and significant body weight gain, parameters prevented by AMY treat- ment. Whereas aortic contractility did not differ in re- sponse to KCl, contractions induced by PHE (1 μ M) as well as relaxation induced by ACh (1 – 30 μ M) or SNP (1 nM – 0.1 mM) on PHE-contracted aorta were decreased ( p < 0.05) in tissues of HFD compared to ND mice, phenomenon significantly ( p < 0.05) diminished in HFD mice treated with AMY. The relaxant actions of ACh and SNP were inhibited ( p < 0.05) by tetraethylammonium (TEA, 5 mM), apamin (0.1 μ M), and 4-aminopyridine (4-AP; 3 mM) in aortae from ND group, but not from HFD. Treatment of HFD mice with AMY rescued the inhibitory effect of TEA ( p < 0.05) on vasorelaxant actions of ACh and SNP. 1H-[1,2,4]oxadiazolo[4,3- a]quinoxalin-1-one (ODQ) inhibited similarly the relaxant effects of SNP in all groups. 8-Br-cGMP relaxed with similar profile aortae of all groups. By preventing HFD- induced obesity in mice, AMY rescued the blunted con- tractile response to PHE, and the attenuated vasorelaxation and K + channel activation (opening) induced by ACh and SNP in isolated aorta.